Arachnoid Cyst as a Late Complication of Selective Dorsal Rhizotomy: A Case Report - van Noort, Maya T.; van Schie, Paul; Slot, K. Mariam; van de Pol, Laura A.; Buizer, Annemieke I.; de Groot, Vincent (Journal of Neurological Surgery Reports, 2024)
Background and importance Selective dorsal rhizotomy (SDR) is a surgical technique to treat spasticity, mainly in children with spastic cerebral palsy (CP). In this report, a unique case of a late arachnoid cyst, causing radiating pain in the left leg, is presented. This is relevant to clinicians managing the long-term follow-up of patients who underwent selective dorsal rhizotomy (SDR).Clinical presentation A 25-year-old male with bilateral spastic CP, who underwent SDR at the age of 7, presented with symptoms of progressive radiating pain in the left leg. Magnetic resonance imaging (MRI) revealed the presence of a large arachnoid cyst and a remarkable dorsal position of the cauda equina. After dissection of the cyst, the previously experienced radiating pain immediately subsided; however, the patient developed urinary retention and constipation. Cauda compression was ruled out by MRI. The constipation subsided quickly, and the patient performed self-catheterization until 1 month postoperatively for the urinary retention after which there were no signs of ongoing bladder dysfunction.Conclusion Arachnoid cyst formation can be a late complication of SDR and can cause lumbosacral radicular syndrome in the late postoperative course in select cases.
Keywords: arachnoid cyst; case report; cerebral palsy; complication; selective dorsal rhizotomy